From "Made in China" to "Innovated in China": Necessity, prospect, and challenges - Wei, Shang-Jin; Xie, Zhuan; Zhang, Xiaobo (American Economic Association, 2017)
After more than three decades of high growth based on its low-wage advantage and relatively favorable demographics--in combination with market-oriented reforms and openness to the world economy--China is at a crossroads with a much higher wage and a shrinking workforce. Future growth will depend, by necessity, more on the generation of increased productivity, and domestic innovation will play an important part in this. In this paper, we assess the likelihood that China can make the necessary transition. Using data on expenditure on research and development, and patent applications, receipts, and citations, we show that the Chinese economy has become increasingly innovative. We will argue that rising wages and expanding markets are among the important drivers of China's growth in innovation. On the other hand, we find evidence of resource misallocation in the innovation area: while state-owned firms receive more subsidies, private firms exhibit more innovation results. Innovation can presumably progress even faster if resource misallocation can be tackled.